Crystal structure of bis-p-anizidinegossypol with an unknown solvate - Honkeldieva, Muhabbat T. (Acta Crystallogr E Crystallogr Commun, 2015)
The title compound, C(44)H(44)N(2)O(8), (systematic name: 1,1′,6,6′-tetrahydroxy-5,5′-diisopropyl-8,8′-bis{[(4-methoxyphenyl)iminiumyl]methyl}-3,3′-dimethyl-2,2′-binaphthalene-7,7′-diolate) has been obtained by the addition of p-anizidine to gossypol dissolved in dichloromethane. In the solid state, the title compound exists in the enamine or quinoid form. The two naphthyl moieties are inclined to one another by 72.08 (5)°. The pendant phenyl rings are inclined at 22.26 (14) and 23.86 (13)° to the corresponding naphthyl rings. In the crystal, molecules are incorporated into layers through inversion-related pairs of O—H⋯O interactions [graph sets R (2) (2)(20) and R (2) (2)(10)] and translation-related O—H⋯O interactions [graph set C(15)]. The packing of these layers in the crystal structure gives rise to channels in the [011] direction, with hydrophobic interactions occurring between adjacent layers. The channels are 5–7 Å wide, and the void volume of each cell is 655 Å(3), corresponding to 26.6% of the cell volume. Disordered guest molecules, probably solvent and water molecules, occupy these voids of the crystal; their contribution to the scattering was removed with the SQUEEZE routine [Spek (2015 ▸). Acta Cryst. C71, 9–18] of PLATON [Spek (2009 ▸). Acta Cryst. D65, 148–155].